ANALYSIS OF BOARDING SCHOOL EDUCATION IN DEVELOPING AUTHONOMY OF ATTAQWA RELIGIOUS STUDENTS - Mista, Hunaidah (Robbayana: Jurnal Pendidikan Agama Islam, 2023)
This research was conducted in male Attaqwa Islamic Boarding School Ujungharapan from July till October 2018 with respondents are students of class XII High school in male Attaqwa Islamic Boarding School on Even Semester of The school years 2017/2018 with the number of respondents are 123student With the level of confidence is 5% and all respondents were selected randomly. All the data collection was done mostly through questionnaire, while interview and observation were also conducted to get complementary data. Data validity and reliability was analysed by Chi Quadrat to get compatibility and significancy among the data tested. This goal of research is to find out the firstly of making use of education resource in development of autonomy student and secondly is the effectivity of boarding based education in creating autonomous student in carrying out. Based on the data gatherer and analyzed,it can be concluded that the process of boarding based education in Male Attaqwa Islamic boarding School is conducted well. This conclusion is derived from the counting x2 > x2 is 113.1. so H1 is accepted and H0 is rejected with a 5% with the level of freedom K-1. This finding was indicated from two indicator of management and system of communicatin which has bigger score than t table and supported from the level student autonomy which has significant score in emotional autonomy (280,790), intellectual autonomy (184,67) and economic autonomy (227,63). Based on above mentioned data, it can be concluded that the concept of boarding based education as applied in male Attaqwa Islamic Boarding school has significantly created autonomous student from the side of emotionality, intellectuality and economy. But form the side of social autonomy the data did not show significant score. This condition is perhaps influenced by the factor of adolescent egocentrism.